Changes Detection of Mangrove Ecosystembased on Obia Method in Liong River, Bengkalis Riau Province - Rosmasita, Rosmasita; Siregar, Vincentius P; Jonniere, Romie; Miswadi, Miswadi (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Status of mangrove ecosystem on Liong River, Bengkalis Island, Riau Province, is currently in a condition that tends to get a stressed doe to 60% of indigenous people living around mangroves are loggers. Series Landsat is used as recording data to map the mangrove and to see the changes in the region. This study aims to map changes in mangrove ecosystems from 1990 - 2017 using the OBIA method. The field observation was done using Unmanned Aerial Vehicle (UAV). The results showed that mangrove area has decreased every year. It was caused by anthropogenic and natural factors. Approximately 4.2% of mangrove decrease from 1990 to 2017 and mangrove highest exploitation occurred in 2007 with a decline of 31.5%.